Major venous resection and reconstruction using a minimally invasive approach during laparoscopic pancreaticoduodenectomy: One step forward. Issue 4 (November 2015) - Palanisamy, Senthilnathan; Deuri, Biswajit; Naidu, Subrahmaneswara Babu; Vaiyapurigoundar Palanisamy, Nalankilli; Natesan, Anand Vijay; Palanivelu, Praveen Raj; Parthasarathy, Ramakrishnan; Palanivelu, Chinnusamy
Abstract: In the current era of technological advancement, the feasibility of laparoscopic pancreaticoduodenectomy has been established. However, major venous resection and reconstruction along with laparoscopic pancreaticoduodenectomy is still considered a complex procedure. A 47‐year‐old woman presented with obstructive jaundice secondary to carcinoma in the pancreatic head. Triphasic abdominal CT revealed a 2.7 × 3.0‐cm heterogenous mass in the pancreatic head with peripancreatic lymphadenopathy without vascular involvement. The patient was scheduled for laparoscopic pancreaticoduodenectomy. During mobilization, the tumor was found adherent to the superior mesenteric vein. Therefore, vascular resection and reconstruction was accomplished laparoscopically along with pancreaticoduodenectomy. The duration of superior mesenteric vein occlusion was 45 min. The patient had an uneventful recovery and was discharged on postoperative day 10. Major venous resection and reconstruction during laparoscopic pancreaticoduodenectomy using a minimally invasive approach is feasible in selected patients. Adequate experience in complex laparoscopic pancreatic surgery is required before attempting this procedure.